2010
DOI: 10.1590/s0103-84782010005000087
|View full text |Cite
|
Sign up to set email alerts
|

Associação de pós inertes com fungo entomopatogênico para o controle do cascudinho (Alphitobius diaperinus)

Abstract: RESUMO O objetivo deste trabalho foi avaliar a eficiência de Beauveria bassiana (Bb), da terra diatomácea (TD) e dos pós de rocha Protesyl e Rocksil, isoladamente ou em associações, para o controle de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(11 reference statements)
0
2
0
1
Order By: Relevance
“…Additionally, the emergence of resistant insect populations can occur (GARG et al, 2004;UEMURA et al, 2008;CHERNAKI et al, 2011). Studies with entomopathogenic fungi (ROHDE et al, 2006;ALVES et al, 2015), insecticidal plants (MARCOMINI et al, 2009;ALVES et al, 2012) and inert powders (SANTORO et al, 2010;ALVES et al, 2012) have shown them to be potential alternatives for insect control. Among the latter, highlight is given to diatomaceous earth (DE).…”
Section: Abstract: Diatomaceous Earth (De) Is An Inert Powdermentioning
confidence: 99%
“…Additionally, the emergence of resistant insect populations can occur (GARG et al, 2004;UEMURA et al, 2008;CHERNAKI et al, 2011). Studies with entomopathogenic fungi (ROHDE et al, 2006;ALVES et al, 2015), insecticidal plants (MARCOMINI et al, 2009;ALVES et al, 2012) and inert powders (SANTORO et al, 2010;ALVES et al, 2012) have shown them to be potential alternatives for insect control. Among the latter, highlight is given to diatomaceous earth (DE).…”
Section: Abstract: Diatomaceous Earth (De) Is An Inert Powdermentioning
confidence: 99%
“…R. communis has developed a natural defense mechanism against insect attack throughout its evolution, including the synthesis and accumulation of substances that are used in its defense as the inhibitor of proteins called ricin, being the main responsible for toxicity in this plant (SANTORO et al, 2010). According to the United States germplasm bank, the concentration of ricin in R. communis leaves may vary between different genotypes, with levels of 1.5 to 9.7 mg / g being detected (PINKERTON et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Não só as plantas são usadas para o controle de insetos praga, outra fonte de estudo são os minerais como os pós de inerte (Santoro et al, 2010). Por serem ricos em silício, são associados também a resistência das plantas ao ataque de pragas e doenças (Korndorfer & Datnoff, 1995).…”
Section: Introductionunclassified